3P Marketing Strategy to Increase Furniture Sales Volume at CV Karya Apik Jombang - Dita Caturani; Suci Prihatiningtyas; Mar'atul Fahimah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Marketing strategy is a very important thing and affects a business or business. A company established not only produces a product or service, the company is certainly required to continue to survive in the long term. Therefore, the company must have a marketing plan or strategy that is made in detail and directed in various related fields, so that it can achieve the right goals and objectives that have been planned from the start. This study aims to determine the marketing strategy to increase the volume of furniture sales at CV Karya Apik Jombang. This research is a survey with qualitative research. Data collection techniques using observation, personal interviews with the director and study documentation. The data analysis technique used is descriptive qualitative analysis method. The results of this study indicate that the marketing strategy consisting of product, promotion and distribution has a positive effect on increasing the volume of furniture sales at CV Karya Apik Jombang.